Analisis Dampak Perubahan Lingkungan Akibat Pembangunan Flyover Ganefo Jalan Raya Mranggen Kabupaten Demak - Zulfa, Rifani; Jabbar, Abdul (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2024)
Infrastructure development aims to improve people's welfare, but can indirectly change land use and environmental conditions. The aim of this research is to analyze the impact of environmental changes resulting from the construction of the Ganefo Flyover on Jalan Raya Mranggen, Demak Regency. The impacts of environmental change studied are in the form of biotic, abiotic and social environments. The impact of the abiotic environment on noise is measured with a Sound Level Meter. The biotic environment for biodiversity is observed using the Rapid Survey method. Community perception data was collected through questionnaires by visiting residents' homes. The results of the analysis show that in the abiotic environment there is a change in the form of a decrease in noise levels, while in the biotic environment there is a change in the form of a decrease in the diversity of vegetation and wildlife. Environmental changes according to public perception are getting better in terms of traffic and road conditions. However, conditions worsened in waterways, air, dust, green open space (RTH) and biodiversity, and did not change in noise conditions. Therefore, it is concluded that after the Ganefo Flyover existed, it had an impact on changes in the surrounding environment.